X-Cut LiNbO3 Optical Modulators Using Gap-Embedded Patch-Antennas for Wireless-Over-Fiber Systems. (23rd October 2012) - Wijayanto, Yusuf Nur; Murata, Hiroshi; Kawanishi, Tetsuya; Okamura, Yasuyuki
Abstract : We propose anx -cut LiNbO3 optical modulator using gap-embedded patch-antennas for wireless-over-fiber systems. The proposed device is composed of an array of narrow-gap-embedded patch-antennas and an optical waveguide located at the center of the gap without a buffer layer. The modulation efficiency of the proposedx -cut LiNbO3 optical modulators was enhanced by 6 dB compared to thez -cut LiTaO3 -based devices.